Airborne particulates (PM10) and tracheal mucus: A case–control study at an American Thoroughbred racetrack. (15th August 2014) - Millerick‐May, M. L.; Karmaus, W.; Derksen, F. J.; Berthold, B.; Robinson, N. E.
Summary: Reasons for performing study: Particle mapping within stalls has demonstrated a relationship between particulate concentrations and visible accumulations of tracheal mucus. However, measurement of breathing zone particulate concentrations, which is the most accurate way to measure exposure, has not been performed to determine the relationship between exposures and accumulations of tracheal mucus sufficient to affect performance. Objectives: To compare breathing zone particulate exposures between horses with tracheal mucus scores (MS) previously demonstrated to affect performance (MS≥2) and those without (MS = 0) visible tracheal mucus. Study design: Case–control study. Methods: We endoscopically examined 649 Thoroughbred racehorses over 7 months and selected 113 age‐matched cases and controls based on the presence (MS≥2) or absence (MS = 0) of tracheal mucus, respectively. Inflammatory cell numbers in tracheal lavage were also determined. Breathing zone monitors recorded particulate exposure during 3 time periods (mid‐day, evening and overnight). Total recording time averaged 17.5 h/horse. Results: The overall prevalence of MS≥2 in the observed stables was 23%. Breathing zone particular matter (PM10) concentrations were very similar to previously reported ambient concentrations. During the evening and overnight, cases had significantly higher breathing zone PM10 concentrations and neutrophil counts than controls. Inflammatory cell counts were associated with average PM10 concentrations throughout the day. Conclusions: Breathing zone particulate concentrations are associated with MS≥2 and inflammatory cell numbers. If breathing zone particulate exposures are predominantly influenced by ambient PM concentrations, racing stable management practices to reduce particle exposures should greatly reduce the prevalence of tracheal mucus.